Роль региональных элит и столичного эстеблишмента в формировании властной элиты Украины - Зоткин, А. (Социология: теория, методы, маркетинг, 2004)
The author discusses a power elite formation process in Ukraine, studies the regional and capital dynamics of this process. The main capitals and strategies of regional elite "fighting for Kyiv" along with the evolution role of the capital establishment played in the inner life of this country are reviewed.